T Ikatan Baja Tulangan Pada Beton Pond Ash Sebagai Pengganti Sebagian Pasir - Tumingan Tumingan; Salma Alwi (Jurnal Poli-Teknologi, 2020)
Pond ash concrete bond is expected to increase bond strength, because in previous studies pond ash concrete resulted in increased mechanical properties of concrete. Bond strength is the bonding mechanism between steel reinforcement and concrete in reinforced concrete construction as the main tool to transfer internal strength between reinforcement and concrete. In this study, a total of thirty-six cylinder concrete with a diameter of 15 cm and a height of 30 cm. Variations of the test parameters are three reinforcement diameters of 12 mm, 16 mm and 25 mm and two types of reinforcement namely plain reinforcement and deform reinforcement for normal concrete and pond ash concrete, using a 25 MPa normal concrete mix design and water cement ratio of 0.52. The results showed that the increase in bond strength on the plain reinforcement from 84.49 kg/cm2 to 91.33 kg/cm2 an increase of 8.09%, while for deform reinforcement there was in increase from 119.70 kg/cm2 in concrete normal to 131.32 kg/cm2 an increase of 9.71% in pond ash concrete. Split collapse occurs in deform reinforcement, whereas in plain reinforcement, slip collapse occurs.